Prevalence of Anxiety and Depression Symptoms in People with Carpal Tunnel Syndrome - Henver Ribeiro Paiva Filho; Franco Luiz Cabral Pedroso; Fernando Brito Bueno; Valdênia Graças Nascimento Paiva; Elias Felix Oliveira; Murilo Antônio Rocha (Revista Brasileira de Ortopedia)
Abstract Objectives To demonstrate the prevalence of depression and anxiety symptoms in patients with carpal tunnel syndrome treated at a hand surgery outpatient clinic and to describe the clinical and epidemiological characteristics of this population. Methods People diagnosed with carpal tunnel syndrome at the initial visit were evaluated over a 6-month period for data collection. Clinical and epidemiological characteristics were noted, and patients diagnosed with anxiety and/or depression were evaluated. Results In total, 101 people had carpal tunnel syndrome, including 38 diagnosed with depression and 29 with anxiety. Most patients were low-income women, with elementary school-level education. More than half of the patients had at least one associated systemic comorbidity. Conclusion Independent characteristics that statistically influenced anxiety and depression symptoms in patients with carpal tunnel syndrome were gender, smoking, and family income (p< 0.05).